Use of stochastic resonance effect for analysis of acoustic radiation spectrum of small unmanned aerial vehicles - Карташов, В.М.; Харченко, О.И.; Чумаков, В.И. (Radiotekhnika, 2019)
Stochastic filtering of acoustic radiation of small unmanned aerial vehicles is considered. Calculation results of an information signal at different noise levels are given. Noise level values are calculated, which ensure the effective selection of the information signal. It is shown that the nonlinear filter based on the effect of a stochastic resonance at a certain noise level provides selection of acoustic radiation of acoustic radiation of small unmanned aerial vehicles. The model of the nonlinear stochastic filter bandwidth regulation by changing coefficient of frequency recalculation is developed.